Needs assessment for Tarbiyah jinsiyah-based biblioeducational group guidance to enhance muslim adolescents’ self-control - Salsabila Ayuning Santi; Henny Indreswari; Khairul Bariyyah (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2026)
Adolescence is a developmental stage marked by increased curiosity, social interaction, and exposure to digital media, which can challenge self-control. However, many students do not yet demonstrate optimal self-control, indicating the need for appropriate guidance interventions. This study aims to explore students’ needs as a preliminary step in developing a group guidance manual using a biblio-education technique integrated with tarbiyah jinsiyah to enhance self-control among Muslim adolescents. This study employed a mixed-method approach with an explanatory sequential design. Quantitative data were collected through a self-control questionnaire, while qualitative data were obtained through interviews with school counselors. Data were analyzed using descriptive and thematic analysis. The findings show that most students have moderate levels of self-control, indicating room for improvement. Students need engaging, relevant, and value-based guidance media, while counselors emphasize integrating Islamic values and narrative-based materials. These findings imply that developing a biblio-education-based group guidance manual integrated with tarbiyah jinsiyah is both necessary and feasible to support adolescents’ self-control development.